Bun Bun Button - Polacco, Patricia (New York : G. P. Putnam's Sons, 2011)
Paige Darling loves the stuffed rabbit her grandmother has made for her, but when she ties a helium-filled balloon to Bun Bun Button the toy gets loose and goes floating away, and it may take some Darling luck to bring her home
Keywords: Toys -- Juvenile fiction; Lost articles -- Juvenile fiction; Grandmothers -- Juvenile fiction; Fortune -- Juvenile fiction; Toys -- Fiction; Lost and found possessions -- Fiction; Luck -- Juvenile fiction; Fiction